Design and conception of photosensitisers - Dumoulin, Fabienne (Springer Netherlands, 2012)
This chapter resumes the general strategies and the last progresses in the design of photosensitisers, with chosen examples, many of them being extracted for the last 5 years literature. © 2018 Elsevier B.V., All rights reserved.